(3GdPNjQIs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3cJH Gdhba s
(3BNQgG (B:s
(3GdaUd GdQGHY ai GdGSJMbGb s
(3ef fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B10 - (3U (B279 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B825s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B34) s
Keywords: (3Gdabg GdeGdcjs